Forging across boundaries - Bereza, Gene Anthony, author; Getty, Nilda C., advisor; Mitchell, Carol A., committee member; Twarogowski, Leroy A., committee member; Jacobs, Peter, committee member; Oleson, Cori M., committee member (Colorado State University. Libraries, 2002)
In this thesis I employ my art as a medium for personal narrative and my outlook of the world. I use forged metal in the majority of the works but I also employ other metalsmithing techniques and include non-metal materials to add a sense of wholeness and variety. The stories recounted in this thesis are about crossing various boundaries that surround us every day. Some of those include boundaries of personal identity, relationships, global concerns, and conformity. Some boundaries are never crossed and perhaps that is best. Although when a boundary set by others into uncharted territory is crossed, new truths can be discovered.
Keywords: Swords; Knives; Metal sculpture, American